Baby Massage Meningkatkan Nafsu Makan Dan Kualitas Tidur Pada Balita - Sayuti, Sayuti; Qotimah, Qotimah; Rokhamah, Rokhamah (Universitas Tribhuwana Tunggadewi, 2023)
Baby massage is applying gentle pressure on the surface of the baby's skin to increase appetite and sleep quality. A preliminary study conducted at Ravanzha baby spa found that out of 15 mothers who had babies, seven had difficulty eating, and eight mothers complained that their children had difficulty sleeping, often woke up, and were fussy at night. This study aims to determine the effect of baby massage on increasing appetite and sleep quality. This type of research is a pre-experimental one-group pre-test-post-test design. The total population of 55 pairs of mothers and toddlers. The 30 mothers and toddlers were selected using a purposive sampling technique with the inclusion criteria of children under five and mothers willing to have children as respondents. The instrument used is the observation sheet. The analysis used a paired t-test. The results showed that there was a significant effect on baby massage the the increase of appetite which was indicated by the value of Tcount Ttable (p = 0.000). In addition, there was an increase in sleep quality with a Tcount = 17.381 Ttable = 1.699. It can be concluded that there is a significant effect of giving a baby massage on increasing appetite and improving sleep quality. Recommendations for further study can measure weight gain for toddlers after being massaged and also perform frequent massages.